2009
DOI: 10.1021/ma901945u
|View full text |Cite
|
Sign up to set email alerts
|

Polyester Synthesis at Moderate Temperatures via the Direct Polycondensation of Dicarboxylic Acids and Diols Catalyzed by Rare-Earth Perfluoroalkanesulfonates and Bis(perfluoroalkanesulfonyl)imides

Abstract: Recently, we reported that scandium trifluoromethanesulfonate [Sc(OTf)3] and scandium trifluoromethanesulfonimide could catalyze polycondensations of dicarboxylic acids and diols. Although these polycondensations were one-step and occurred at the moderate temperature of 35 °C, they required large amounts of the catalysts (ca. 1 mol %) and long reaction times (>100 h). Therefore, scandium catalysts having stronger electron-withdrawing ligands (scandium perfluorooctanesulfonate, scandium nonafluorobutanesulfonat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 31 publications
0
29
0
Order By: Relevance
“…Nf 2 NH was obtained from Mitsubishi Materials Electronic Chemicals (Akita, Japan). Sc(NTf 2 ) 3 and Sc(NNf 2 ) 3 were prepared according to a literature report …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nf 2 NH was obtained from Mitsubishi Materials Electronic Chemicals (Akita, Japan). Sc(NTf 2 ) 3 and Sc(NNf 2 ) 3 were prepared according to a literature report …”
Section: Methodsmentioning
confidence: 99%
“…To the best of our knowledge, no study has dealt with the activation thermodynamics of microwave‐assisted polymerizations, which forms the basis of the study reported herein, in which we characterize the ROP of ε‐caprolactone at relatively low temperatures (50–70 °C) controlled by microwave heating and catalyzed by the super Brønsted acids, trifluoromethanesulfonimide (Tf 2 NH), and nonafluorobutanesulfonimide (Nf 2 NH), and by the Lewis acids, scandium trifluorobutanesulfonimide (Sc(NTf 2 ) 3 ) and scandium nonafluorobutanesulfonimide (Sc(NNf 2 ) 3 ) . These compounds are also effective catalysts of dehydration polycondensations of dicarboxylic acids and diols . To investigate the ROP kinetics of ε‐caprolactone, we performed temperature studies to obtain the Arrhenius and Eyring thermodynamic parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Scandium bis(nonafluorobutanesulfonyl)imide (Sc(NNf 2 ) 3 ) was prepared in our laboratory according to the procedure described in the literature. 26 Measurements 1 H-NMR spectra were recorded at 27 1C using a Bruker Analytik DPX200 spectrometer (Bruker BioSpin, Kanagawa, Japan, 200 MHz). The number-average molecular weight (M n ) and the polydispersity index (M w /M n ) of each polyester were estimated using a size exclusion chromatography system that included a Tosoh DP8020 pump system, an RI (Tosoh, Tokyo, Japan, Tosoh RI-8020) detector and a Tosoh TSKgel SuperMultiporeHZ-M column calibrated with polystyrene standards.…”
Section: Experimental Procedures Materialsmentioning
confidence: 99%
“…Therefore, we next focused on identifying more active catalysts and found that scandium and thulium bis(nonafluorobutanesulfonyl)imide ((Sc(NNf 2 ) 3 ) and (Tm(NNf 2 ) 3 )) were more efficient catalysts and allowed us to obtain high-molecular-weight polyesters (M n 42.0Â10 4 ) from adipic acid (AdA) and 3-methyl-1,5-pentanediol (MPD) at 60 1C in a short period of time (24h) and with a smaller amount of catalyst (0.1 mol%) than had previously been possible. 26 Rapid syntheses that depend on microwave irradiation have attracted interest because they are environmentally benign. Since first reported in 1986, 27,28 microwave irradiation has been used to shorten the reaction time of organic syntheses, to decrease the levels of side products and to improve the yields and/or chemoselectivities of the products.…”
Section: Introductionmentioning
confidence: 99%
“…Fully aliphatic polyesters are biocompatible and enzymatically biodegradable and they are largely used for biomedical applications . Aliphatic polyesters from adipic acid, succinic acid, sebacic acid, and 1,4‐cyclohexane dicarboxylic acid are some of the important examples. Recently, renewable dicarboxylic acid resources based on isohexide, galactaric, mannitol, itaconic, and furan were also explored for the production of greener polyesters.…”
Section: Introductionmentioning
confidence: 99%